A LINGUAGEM DOS DIREITOS HUMANOS NAS OFENSIVAS ANTIGÊNERO: UM ESTUDO DAS FIGURAS DE VÍTIMA, SELVAGEM E SALVADOR NA ERA FARMACOPORNOGRÁFICA - Mariano, Gustavo Borges (Revista Direito e Sexualidade, 2024)
As anti-gender campaigns have been rising in Portugal since 2018; in this paper, I will analyze how human rights discourses are deployed in speeches mainly from two different events: a debate held on TV and an online streamed seminar. The aim is to analyze the figures of the child, trans* people, the parents and the State created within said discourse. I assess the Portuguese anti-gender discourse with Makau Mutua’s metaphor of the savage, the victim, and the savior and with Paul Preciado’s critique of the pornographic logic to understand the discursive formations. The conveyed images were: the child-victim as in need of protection, the parents as both victim and savior, and the trans* person as the savage (along with the State). Human rights are mobilized as a biofictional tool that positions people within that equation and reinforces prostheses of subjectivities to exploit parents’ excitement for omnipotent control through the subordination of children and abjection of trans*.